Current status of Helicobacter pylori resistance to Clarithromycin and Levofloxacin in Malaysia—findings from a molecular based study - Suat Moi Puah; Khean Lee Goh; Heng Kang Ng; Kek Heng Chua (PeerJ, 2021)
Background Resistance to clarithromycin and levofloxacin in Helicobacter pylori which resulted in treatment failures has become a major challenge for physicians worldwide. The resistance is mainly mediated by mutations in a specific domain of the 23S rRNA, gyrA and gyrB genes for clarithromycin and levofloxacin respectively. Hence in this study, we aimed to investigate the current status of H. pylori resistance in our hospital to these two antibiotics based on the molecular approach. Materials and Methods Gastric biopsy samples were obtained from treatment-naïve patients. Bacterial genomic DNA was extracted using a commercial kit and continued with DNA amplification using polymerase chain reaction (PCR) with specific primers. The PCR amplicons were subjected to sequencing on 23S rRNA gene targeting nucleotide positions at 2,146, 2,147, 2,186 and amino acids at gyrA positions 87 and 91 and gyrB positions 436, 438, 481, 484 to investigate the possible mutations or polymorphisms of genes that lead to clarithromycin and levofloxacin resistance respectively. Results Sixty-one urease-positive gastric biopsy samples were studied. The findings revealed the primary resistance rates to clarithromycin was 14.8% and to levofloxacin was 3.3% in our current scenario based on detection of reported resistance-related mutations of A2147G and D91N in 23S rRNA and gyrA genes, respectively. Interestingly, we found a high rate of silent mutations of the gyrA codon 87Asn (32.8%, 20/61) and two polymorphisms of the gyrB D481E (16.4%, 10/61) and R484K (21.3%, 13/61). The role of these polymorphisms in gyrB remained to be elucidated whether the levels of levofloxacin resistance are related to the position/amino acid. Conclusion The primary resistance rate of H. pylori to clarithromycin has increased compared to the previous report in Malaysia. Therefore, molecular screening could aid and is important for the selection of antibiotics for H. pylori eradication therapies.